2013
DOI: 10.1155/2013/525326
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of AO Type C Fractures of the Distal Part of the Humerus through the Bryan-Morrey Triceps-Sparing Approach

Abstract: Several alternative approaches have been described to avoid the complications related to the olecranon osteotomy used to treat distal articular humerus fractures. The published experience with the triceps-sparing approach is scant. In this prospective study, a total of 12 patients with an articular humeral fracture were treated using this approach. At a mean followup of 1,7 years, the average range of motion was 112.8° (range from 85° to 135°); the elbow flexion averaged 125.5° (range from 112° to 135°) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
1
9
0
2
Order By: Relevance
“…compared triceps sparing with olecranon osteotomy approach in 67 patients with type C distal humerus fracture in an elderly population and concluded that triceps-sparing group has better functional outcomes, faster patient recovery, and lower complication rate, all without compromising visibility of articular surface or impairing fracture reduction during fixation 23. In our study, the mean MEPI score was 94.40 point, with 17 excellent, five good, three fair, and no poor grade, which is consistent with other published series 3102225. In 21 patients, the muscle strength was normal and four patients had good muscle strength when compared to the uninjured arm.…”
Section: Discussionsupporting
confidence: 89%
“…compared triceps sparing with olecranon osteotomy approach in 67 patients with type C distal humerus fracture in an elderly population and concluded that triceps-sparing group has better functional outcomes, faster patient recovery, and lower complication rate, all without compromising visibility of articular surface or impairing fracture reduction during fixation 23. In our study, the mean MEPI score was 94.40 point, with 17 excellent, five good, three fair, and no poor grade, which is consistent with other published series 3102225. In 21 patients, the muscle strength was normal and four patients had good muscle strength when compared to the uninjured arm.…”
Section: Discussionsupporting
confidence: 89%
“…Dental trauma (DT) is a significant public health problem because of its frequency, impact on economic productivity, and quality of life . DT affects mainly youngsters and schoolchildren (8‐11 years old), and its prevalence ranges from 7.4% to 58% . Normally, the most commonly involved teeth are the maxillary incisors, both permanent and deciduous .…”
Section: Discussionmentioning
confidence: 99%
“…In arthroplasty, additional ipsilateral diaphyseal lesions or present implants in the olecranon, the triceps-sparing approaches have showed clinical and technical advantages [39].…”
Section: Approaches For Partially Articular Fracturesmentioning
confidence: 99%